Design and Analysis of 3D Printed Slotted Waveguides for D-Band using Stereolithography and Electroless Silver Plating - Lomakin, Konstantin; Sippel, Mark; Helmreich, Klaus; Gold, Gerald (2020 IEEE/MTT-S International Microwave Symposium (IMS), 2020)
This work demonstrates the feasibility of entirely additively manufactured slotted waveguides in combination with an electroless silver plating process for applications in the D-Band frequency range. Design rules are adjusted towards the requirements for 110-170 GHz and analyzed with respect to the limitations of conventional desktop SLA- and DLP printers. Measurements obtained in this work reach attenuation levels in the order of 20-35 dB/m, hence comparable to conventionally manufactured waveguides. Furthermore, it is shown, that the electrical behavior of slotted waveguides is similar to a conventional waveguide by comparison with simulation model